Multi-Omics Reveal the Efficient Phosphate-Solubilizing Mechanism of Bacteria on Rocky Soil - Ding, Yanqiang; Yi, Zhuolin; Fang, Yang; He, Sulan; Li, Yuming; He, Kaize; Zhao, Hai; Jin, Yanling (Frontiers in Microbiology, 2021)
Phosphate-solubilizing bacteria (PSB) can alleviate available phosphorus (AP)-deficiency without causing environmental pollution like chemical phosphate fertilizers. However, the research and application of PSB on the barren rocky soil is very rare. We screened 6 PSB from sweetpotato rhizosphere rocky soil. Among them, Ochrobactrum haematophilum FP12 showed the highest P-solubilizing ability of 1085.00 mg/L at 7 d, which was higher than that of the most reported PSB. The assembled genome of PSB FP12 was 4.92 Mb with P-solubilizing and plant growth-promoting genes. In an AP-deficient environment, according to transcriptome and metabolomics analysis, PSB FP12 upregulated genes involved in gluconic acid synthesis and the tricarboxylic acid cycle, and increased the concentration of gluconic acid and malic acid, which would result in the enhanced P-solubilizing ability. Moreover, a series of experiments in the laboratory and field confirmed the efficient role of the screened PSB on significantly increasing AP in the barren rocky soil and promoting sweetpotato yield. So, in this study, we screened highly efficient PSB, especially suitable for the barren rocky soil, and explored the P-solubilizing mechanism. The research will reduce the demand for chemical phosphate fertilizers and promote the environment-friendly agricultural development.